Analisa Peranan Kualitas Laba Terhadap Ketahanan Keuangan Pada CV. Rhoda Jaya Surabaya - Aya Soraya; Abelia Fojroyur Rohman; Wulan Nur Maulida; Maria Yovita R. Pandin (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This research was carried out to determine the impact of earnings quality on financial resilience at CV. Rhoda Jaya. The qualitative methodology used in this research is by conducting interviews, observations, notes regarding problems, and other data sources against company informant CV. Rhoda Tiga. The data management stages start with the first data collection, second data triangulation, third Data reduction, fourth, presentation of data and finally, verification and conclusions. For data analysis methodsThe research uses a narrative analysis approach where the researcher constructs a narrative or story from the collected data.